Longitudinal reproducibility of default-mode network connectivity in healthy elderly participants: A multicentric resting-state fMRI study - Jovicich, Jorge; Minati, Ludovico; Marizzoni, Moira; Marchitelli, Rocco; Sala-Llonch, Roser; Bartrés-Faz, David; Arnold, Jennifer; Benninghoff, Jens; Fiedler, Ute; Roccatagliata, Luca; Picco, Agnese; Nobili, Flavio; et al. (NeuroImage (Orlando, Fla.), 2016)
To date, limited data are available regarding the inter-site consistency of test–retest reproducibility of functional connectivity measurements, in particular with regard to integrity of the Default Mode Network (DMN) in elderly participants. We implemented a harmonized resting-state fMRI protocol on 13 clinical scanners at 3.0T using vendor-provided sequences. Each site scanned a group of 5 healthy elderly participants twice, at least a week apart. We evaluated inter-site differences and test–retest reproducibility of both temporal signal-to-noise ratio (tSNR) and functional connectivity measurements derived from: i) seed-based analysis (SBA) with seed in the posterior cingulate cortex (PCC), ii) group independent component analysis (ICA) separately for each site (site ICA), and iii) consortium ICA, with group ICA across the whole consortium. Despite protocol harmonization, significant and quantitatively important inter-site differences remained in the tSNR of resting-state fMRI data; these were plausibly driven by hardware and pulse sequence differences across scanners which could not be harmonized. Nevertheless, the tSNR test–retest reproducibility in the consortium was high (ICC=0.81). The DMN was consistently extracted across all sites and analysis methods. While significant inter-site differences in connectivity scores were found, there were no differences in the associated test–retest error. Overall, ICA measurements were more reliable than PCC-SBA, with site ICA showing higher reproducibility than consortium ICA. Across the DMN nodes, the PCC yielded the most reliable measurements (≈4% test–retest error, ICC=0.85), the medial frontal cortex the least reliable (≈12%, ICC=0.82) and the lateral parietal cortices were in between (site ICA). Altogether these findings support usage of harmonized multisite studies of resting-state functional connectivity to characterize longitudinal effects in studies that assess disease progression and treatment response. •We implement a multi-site 3T MRI protocol for resting state fMRI in 13 sites.•We acquire across-session test–retest (TRT) data on 64 healthy elderly participants.•Despite harmonization strong phantom and brain tSNR differences remain across sites.•TRT error of regional DMN functional connectivity is consistent across sites.•ICA yields more reliable DMN connectivity measurements relative to SBA.